1991
DOI: 10.1128/jb.173.20.6537-6546.1991
|View full text |Cite
|
Sign up to set email alerts
|

Erwinia carotovora subsp. carotovora extracellular protease: characterization and nucleotide sequence of the gene

Abstract: The prtl gene encoding extracellular protease from Erwinia carotovora subsp. carotovora EC14 in cosmid pCA7 was subcloned to create plasmid pSK1. The partial nucleotide sequence of the insert in pSK1 (1,878 bp) revealed a 1,041-bp open reading frame (ORF1) that correlated with protease activity in deletion mutants. ORF1 encodes a polypeptide of 347 amino acids with a calculated molecular mass of 38,826 Da. Escherichia coli transformed with pSKI or pSK23, a subclone of pSK1, produces a protease (Prtl) intracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
2

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 61 publications
1
19
0
2
Order By: Relevance
“…38,000 ( Fig. 2A), which is similar to the molecular sizes of proteases that are described for other bacterial pathogens (5,21). However, it is 10 kDa smaller than the proteases produced by Erwinia amylovora (35) and V. vulnificus (24).…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…38,000 ( Fig. 2A), which is similar to the molecular sizes of proteases that are described for other bacterial pathogens (5,21). However, it is 10 kDa smaller than the proteases produced by Erwinia amylovora (35) and V. vulnificus (24).…”
Section: Resultssupporting
confidence: 76%
“…2B, panel a) revealed the presence of a single band with 4.4 as an isoelectric point of the native protein. This value is lower than pIs reported for various other proteases, such as those expressed by several marine vibrio species (5) and P. carotovorum (21). Zymogram analysis of the preparation separated by isoelectric focusing showed that proteolytic activity was associated with the Coomassie blue-stained band (Fig.…”
Section: Resultsmentioning
confidence: 57%
“…A 100-kDa sequence of Ca 2ϩ -dependent bacteriocin that was involved in the consensus RTX sequence in Rhizobium leguminosarum was encoded by a single gene that was unlinked to any of the activity regulator genes (30). The RTX-like metalloprotease produced by Erwinia carotovora also was encoded by the prt1 gene alone, and the expression of prt1 itself, in recombinant E. coli cells, showed a high level of protease activity (20). In both PnxIA and PnxIIA, putative acylation sites that were found in strongly cytotoxic types of RTX toxins (36) were found not to be involved.…”
Section: Discussionmentioning
confidence: 98%
“…One of these proteinases, extracted from Erwinia carotovora subsp. carotovora, is similar in its properties to thermolysin from Bacillus thermoproteolyticus [32]. BIOCHEMISTRY (Moscow) Vol.…”
mentioning
confidence: 97%